Flavor Preferences Conditioned by Dietary Glutamate(1)(2)(3) - Ackroff, Karen (Adv Nutr, 2016)
Our understanding of the molecular basis of umami taste and its appetitive qualities has been greatly aided by studies in laboratory rodents. This review describes methods for testing responses to the prototypical umami substance monosodium glutamate (MSG) in rodents. Two techniques, forced exposure to MSG and 2-bottle choice tests with ascending concentrations, were used to evaluate the responses to the taste of umami itself, and 2 other methods used oral or postoral MSG to modify the responses to other flavors. Intake and preference for MSG are enhanced in mice by experience with MSG and with other nutrients with positive postoral effects. In addition, flavor preferences are enhanced in mice and rats by gastric or intestinal MSG infusions via an associative learning process. Even mice with an impaired or absent ability to taste MSG can learn to prefer a flavor added to an MSG solution, supporting the notion that glutamate acts postorally. The more complex flavor of dashi seasoning, which includes umami substances (inosinate, glutamate), is attractive to rodents, but dashi does not condition flavor preferences. Details of the postoral glutamate detection process and the nature of the signal involved in learned preferences are still uncertain but probably involve gastric or intestinal sensors or both and vagal transmission. Some findings suggest that postoral glutamate effects may enhance food preferences in humans, but this requires further study.